Potential benefits of JAK inhibitor therapy in Blau syndrome: a case report - Wang, Yu; Yu, Xiao-juan; Zhang, Zhuoli (Frontiers in Immunology, 2026)
Blau syndrome is a rare autoinflammatory disorder caused by gain-of-function mutations in the NOD2 (nucleotide binding oligomerization domain containing 2 receptor) gene. Blau Syndrome presents with the diagnostic triad of chronic polyarticular synovitis, recurrent uveitis, and dermatitis. Notably, patients often develop systemic granulomatous inflammation affecting multiple organs, particularly the kidney and liver. Here we report a case of Blau syndrome presented with early-onset arthritis, uveitis, and renal involvement, evidenced by granulomas tubulointerstitial nephritis. Genetic testing showed a pathogenic p.R334W NOD2 mutation demonstrating constitutive NF-κB activation and excessive proinflammatory cytokine production. While initial corticosteroid therapy improved articular and ocular symptoms, renal dysfunction persisted until baricitinib (4 mg/day) initiation, which rapidly normalized renal function and permitted steroid tapering. Granulomatous inflammation in Blau syndrome is mediated by IFN-γ and sustained JAK-STAT activation, making JAK1/2 inhibition a rational therapeutic target. Although TNF-α inhibitors show efficacy in some cases, our experience supports baricitinib’s potential for refractory disease, particularly with renal involvement. Baricitinib can offer distinct advantages over biologics and effectively downregulates inflammation in Blau syndrome.